Early growth of imperial palm (Roystonea oleracea) in tropical environments - Monteiro, Victória Azevedo; Gomes, Francielly Rodrigues; Ragagnin, Angelita Lorrayne Soares Lima; Somera, Andreia; Silveira Neto, Américo Nunes da; Assunção, Hildeu Ferreira da; Hurtado-Salazar, Alejandro; Silva, Danielle Fabíola Pereira da (Revista de Ciencias Agrícolas, 2025)
The imperial palm (Roystonea oleracea (Jacq.) O.F.Cook) was first introduced to Brazil in 1809 as a gift to King Dom João VI, subsequently becoming a favored ornamental species. Its aesthetic appeal, grandeur, and adaptability have contributed to its widespread use in urban landscaping across the country. Despite its prominence, scientific studies on its physiological development under tropical conditions remain limited. Therefore, the objective of this work was to evaluate the growth of plants and the chlorophyll content of the imperial palm leaves. The experiment was carried out at the Federal University of Jataí, where 56 plants of Roystonea oleraceae transplanted to the university's central seedbed at 95 months in 2017 were evaluated. Plant growth data were collected on 11/14/2017, 06/28/2017, 2018, and 11/24/2018, and the plants were evaluated for height, diameter, and number of leaves. Analyses were also carried out regarding the chlorophyll content on 08/18/2018 and 11/24/2018 using a completely randomized design with 56 replications. Through descriptive statistics, the growth and chlorophyll content data were analyzed. The initial development of Roystonea oleracea under tropical conditions demonstrated a vigorous growth pattern, particularly in plant height, which increased from an average of 86.36 cm to 151.19 cm over seven months. Stem diameter exhibited a consistent upward trend, with averages progressing from 22.04 cm to 36.64 cm, and reaching 37.08 cm in the final assessment. These findings suggest that R. oleracea adapts well to the environmental conditions of the study site, showing promising potential for ornamental and ecological applications in tropical urban landscapes.